Myofascial pain disorder: A narrative review - Chieh Chen; Da-Ming Liao (Tungs’ Medical Journal)
The term “myofascial pain” was first coined by American researcher Dr. Travell in 1952. Myofascial pain syndrome (MPS) is characterized by myofascial trigger points and fascial contraction. MPS has received much attention from physicians. With the available treatment options, patients should be encouraged to face their fear and actively cooperate in their treatment to promptly eliminate painful trigger points and treat MPS. Scientific and standardized exercise, excellent living habits, and early therapy are key to early recovery from MPS.